Negative Emotional States and Clinical Variables in People with Human Immunodeficiency Virus/AIDS - Yamila Ramos Rangel; Ana Esther Cabrera Pérez; Belkis González Aguiar (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Foundation: At present it observed an accelerated increase of people who live with Human Immunodeficiency Virus/Aids. This constitutes one of the main challenges which health professionals and researchers have had to face. Objective: to describe the relationship between clinical and psychological variables in people with the diagnosis of Aids. Methods: descriptive correlational study. It was worked with a universe, formed by 19 people diagnosed with Aids. Socio-demographic, clinical and psychological variables were analyzed. A semi- structured interview, State-trait anxiety inventory, Beck depression inventory and State-Trait Anger Expression Inventory. Results: predominating age range were young adults (31.5 %= and middle age (31.5 %) most of them males (74 %) white (14%) with low educational levels (57.9 %). There was a direct correlation between CD4 count and anxiety as a state, anger status trait, anger expression index and depression. Conclusion: there are interlinks among the studied psychological and clinical variables, strong associations among them were found. In the majority of the cases the correlation was strong and direct, except in anxiety as a trait which showed an inverse correlation and very weak with respect to the CD4 count.